1994
DOI: 10.1159/000119084
|View full text |Cite
|
Sign up to set email alerts
|

Fine Motor Performance in Schizophrenia

Abstract: Peripheral and central aspects of motor dysfunction were assessed in 12 schizophrenic and 12 normal subjects, using a test of control of finger movement based on the widely used smooth pursuit eye movement task. This was performed in order to investigate the basis of neuromotor dysfunction in schizophrenia. In this task, subjects used finger movement to track a visual target. Simultaneously, an electromyogram of the extensor digitorum commu-nis, the primary muscle utilized in the task, was recorded. Smooth pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…C ognitive deficits in schizophrenia include impaired attention (Franke et al, 1994;Nuechterlein and Asarnow, 1989) and executive functions (Rund and Borg, 1999), particularly cognitive flexibility and forward planning (Morice and Delahunty, 1996); and motor abnormalities (Wolff and O'Driscoll, 1999), including fine motor skills (Griffith et al, 1994;Vrtunski et al, 1989). Cognitive abnormalities may be present long before illness onset in individuals who develop schizophrenia (Cuesta et al, 2001).…”
mentioning
confidence: 99%
“…C ognitive deficits in schizophrenia include impaired attention (Franke et al, 1994;Nuechterlein and Asarnow, 1989) and executive functions (Rund and Borg, 1999), particularly cognitive flexibility and forward planning (Morice and Delahunty, 1996); and motor abnormalities (Wolff and O'Driscoll, 1999), including fine motor skills (Griffith et al, 1994;Vrtunski et al, 1989). Cognitive abnormalities may be present long before illness onset in individuals who develop schizophrenia (Cuesta et al, 2001).…”
mentioning
confidence: 99%
“…Previous studies have reported that persons with schizophrenia show slower motor performance in the pegboard tasks [10,11], poorer performance in the finger tracking task [12], and impaired motor dexterity on a finger movement test [11] compared to normal controls. All those tasks measure the speed and accuracy of the hand movement performance.…”
Section: Introductionmentioning
confidence: 94%